2012
DOI: 10.1097/sle.0b013e31824f8ae4
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Use of Diclofenac in Combination With Ketamine in Patients Undergoing Laparoscopic Cholecystectomy

Abstract: The preemptive administration of a combination of low-dose ketamine plus diclofenac sodium improved postoperative analgesia after laparoscopic cholecystectomy, whereas ketamine at a dose of 0.15 mg/kg did not elicit a preemptive analgesic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Nesek-Adam et al 20 found the ketamine can decreased the postoperative pain at 12 h postoperatively in abdomen while the postoperative pain score during 12 -24 h postoperatively was higher in ketamine group than that in control group. These study results of Nesek-Adam et al 20 were all no statistically significant. Lenzmeier et al 19 and Reza et al 13 assessed the postoperative pain scores of ketamine at a dosage of 0.50 mg/kg.…”
Section: Postoperative Pain Scorementioning
confidence: 99%
See 4 more Smart Citations
“…Nesek-Adam et al 20 found the ketamine can decreased the postoperative pain at 12 h postoperatively in abdomen while the postoperative pain score during 12 -24 h postoperatively was higher in ketamine group than that in control group. These study results of Nesek-Adam et al 20 were all no statistically significant. Lenzmeier et al 19 and Reza et al 13 assessed the postoperative pain scores of ketamine at a dosage of 0.50 mg/kg.…”
Section: Postoperative Pain Scorementioning
confidence: 99%
“…According to inclusion criteria in our analysis, a total of five English studies 13,[17][18][19][20] matched the selection criteria finally (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations